Ketahanan, Identitas Diri, Remaj HUBUNGAN RESILIENCE DENGAN PENGENALAN DIRI SENDIRI SAAT USIA DEWASA - Indah Mukarromah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2018)
Resilence adolecents could positively respond when deal with difficulties in order to got stronger and easier to realized their identity, till had goals and characters especially who lived in the Orphanage. About 8 of them suffered from self-identity problems such as low self-esteem, didn’t knew their ability, and enclosed. It aimed to analyze the relationship resilience with the self-identity of adolescents lived in orphanages. Type of the research descriptive analytic, cross sectional method and used total sampling (21 adolecents). Resilience scale used to independent variables and self-identity scale used to dependent variables. Fisher's exact test results that p = 0,030 (p ? ?) and r = 0,463, shown there was correlation between resilience with adolescents self-identity, had positive directional correlation and strong enough strength means that adolecents who most resilience could most had positive self-identity itself. Resilience contributed to realized a positive self-identity that influenced by self-power, social support, and interpersonal competence of adolescents. Unresilience adolecents and their negative self-identity needed to be given periodic consultations to be able passed their developmental role, especially those lived in the Orphanage.